Percepção da qualidade de vida relacionada à visão e sintomas de depressão em pacientes com retinocoroidite supostamente toxoplásmica - Jacqueline Souza Dutra (2016)
Introduction: Retinochoroiditis is the main clinical manifestation of toxoplasmosis and may impact on visual function and vision-related quality of life (VRQL). There are few studies of VRQL in these individuals, with conflicting results. Recent evidence also points to the association between toxoplasmosis and neuropsychiatric disorders. Objective: To investigate individual perception on VRQL and prevalence/severity of depression in patients with toxoplasmic retinochoroiditis (TR) seen at a uveitis referral center in Brazil. Methods: Comparative observational cross-sectional study. NEI-VFQ-25 and BDI-II questionnaires were applied to respectively assess VRQL and depression in 207 individuals with TR seen at the Uveitis Unit of Hospital São Geraldo/HC-UFMG and 211 controls between September/2014 and June/2015. Clinical and demographical data were collected during the same visit. Epidata and SPSS softwares were used for descriptive and analytic statistics, with p<0.05. Results: 190 individuals with TR (50.3%) and 188 paired controls (49,7%) were eventually included in the study. All 190 patients with TR and 102/182 (56.0%) control individuals had serum IgG antibodies to T. gondii. Among patients with TR, 63/188 (33.5%) had best corrected visual acuity (BCVA) 20/200 in one eye. TR was bilateral in 56/189 (28.8%), macular in 60/188 (31.9%) and active in 98/188(52.1%). Prior recurrences of TR were reported by 99/188 (52.7%). Among controls, only 2/188 (1.1%) had BCVA <20/63 and >20/200 in one eye; monocular vision was noted in 1.6% (3/188). VRQL scores for all subscales were significantly lower in individuals with TR when compared to controls. These lower VRQL scores were particularly associated with female sex (p=0.004), history of prior TR recurrences (p=0.02), concomitant use of systemic corticosteroids (p=0.008), monocular vision (p<0.001) and blindness (BCVA 20/200 in the better-seeing eye) p<0.001. Individuals with active, bilateral or macular TR also had lower VRQL scores, although not statistically significant (p>0.05). Depression was more prevalent among patients with TR (55/189; 29.1%) than among controls (35/188; 18.6%)p=0,023, also being associated with lower VRQL scores (p<0.001). Controls seropositive and seronegative for toxoplasmosis had similar VRQL scores (p=0.983) as well as comparable rates of depression (p=0.238). Conclusion: TR affects VRQL in Brazilian individuals, particularly in women, using systemic corticosteroids, with significant visual dysfunction and recurrences of TR. Nearly one third of patients with TR had evidence of depression, which was also associated with lower VRQL scores. Neuropsychiatric assessment of these individuals may be warranted.